(untitled) - Droste, Ronald L. (New York, 1997)
This book details the technologies used in water and wastewater management today, including standard practice and state of the art. Its main focus is on the mechanics of processes to treat water or wastewater.
Keywords: Water,Sewage; Purification,Purification